Keeping chickens : getting the best from your chickens - Hobson, J. C. Jeremy; Lewis, Celia, 1948- (Newton Abbot : David & Charles, 2010)
Introduces the physical characteristics, behavior, and life cycle of chickens and offers practical advice on everything from egg-laying and maintaining a healthy hen house to egg incubation and healthcare.
Introduction -- Understanding chickens -- What to consider -- Choosing the breed -- Breeds -- Where & when to get your chickens -- Housing & cleaning -- Feeding chickens -- Breeding chickens -- All about eggs -- Health & care -- Showing.
Previous ed.: 2007.
Includes index.
Keywords: Chickens